1987
DOI: 10.1042/bj2480539
|View full text |Cite
|
Sign up to set email alerts
|

The effects of selenium and copper deficiencies on glutathione S-transferase and glutathione peroxidase in rat liver

Abstract: Selenium (Se) deficiency in rats produced significant increases in the activity of hepatic glutathione S-transferase (GST) with 1-chloro-2,4-dinitrobenzene as substrate and in various GST isoenzymes when determined by radioimmunoassay. These changes is GST activity and concentration were associated with Se deficiency that was severe enough to provoke decreases of over 98% in hepatic Se-containing glutathione peroxidase activity (Se-GSHpx). However, decreases in hepatic Se-GSHpx of 60% induced by copper (Cu) de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 28 publications
(31 reference statements)
1
21
0
Order By: Relevance
“…The current study demonstrates that endogenous factors generated in i o by oxidative stress induced by I\R increase the expression of rGSTA1\A2. In other studies in i o it was found that oxidative stress secondary to selenium deficiency or generated by exercise also increased the expression of rGSTA1\A2 [39][40][41]. Therefore increases in the hepatic expression of some alpha class GSTs are a consistent feature of oxidative stress both in i o and in itro.…”
Section: Discussionmentioning
confidence: 88%
“…The current study demonstrates that endogenous factors generated in i o by oxidative stress induced by I\R increase the expression of rGSTA1\A2. In other studies in i o it was found that oxidative stress secondary to selenium deficiency or generated by exercise also increased the expression of rGSTA1\A2 [39][40][41]. Therefore increases in the hepatic expression of some alpha class GSTs are a consistent feature of oxidative stress both in i o and in itro.…”
Section: Discussionmentioning
confidence: 88%
“…Glutathione peroxidase activity in homogenates prepared from 0.5 cm colon segments ( n = 3) was determined using a glutathione reductase coupled assay with 0.25 mM H 2 O 2 and 5 mM glutathione as substrates [18]. A unit of cytosolic glutathione peroxidase is defined as that which oxidises 1 μmol of NADPH per min.…”
Section: Methodsmentioning
confidence: 99%
“…The GSTs are a group of dimeric enzymes with several biochemical functions, the most important of which is probably detoxification. The major GST subunits in the rat are Ya, Yb1, Yb2 and Yc; the Ya and Yc subunits belong to the Alpha class and the Yb1 and Yb2 subunits belong to the Mu class [11,121. Using specific radioimmunoassay we have shown that Se deficiency increases the hepatic content of each of these subunits [13]. Rat liver also contains small amounts of the Yf subunit of the Pi class, but this subunit has been shown by immunohistochemistry to be present in the biliary epithelia and not the hepatocyte.…”
Section: Introductionmentioning
confidence: 93%